Etnobotani: Pengetahuan Masyarakat Desa Tabangame dalam Pemanfaatan Tumbuhan Obat - Sahil, Isran; Juniartin, Juniartin (IAIN Ternate, 2023)
Traditional knowledge of rural communities about medicinal plants should be documented by academics ar researchers and even local people as a legend from their ancestors that should be protected and preserved. The method used in this study is using descriptive qualitative method, data collection techniques through free interviews purposive sampling technique. Respondents in this study consisted of village heads who represented the community and had knowledge of medicinal plants, a healer as a person who often treated sick people and one patient who shared his experiences when using medicinal plants to treat his illness. The research method above can be explained as follows: (1) Interviews were conducted with the people of Tabangame Village to find out the types of plants, their processing and use as traditional medicine, (2) The local name, its characteristics, the parts used, how to use it and how it is used are recorded, (3) Documentation of each plant used by the community as a treatment. There are four types of plants used for traditional medicine, namely jatropha or balacai (Jatropha curcas L) can treat shortness of breath, poison and internal medicine, betel nut or siri (Piper betle) can treat hives , Matoa or motoa (Pometia Pinnata) can treat ulcers and itching and cashew or yakis fruit (Anacardium occidentale) can treat cough. Keywords: Medicinal Plants, Tabangame Village, Tradisional Knowledge